Fourier Transform Infrared Spectroscopy and Fluorescence Emission Spectroscopic Investigations on Rat Tissue - T.S. Aishwarya1, S. Gunasekaran2, G. Sankari1*, (Recent Research in Science and Technology, 2010)
Fluorescence spectroscopy is an emerging technology in the study of biological samples like tissues. When a tissue sample is illuminated with specific wavelength of UV or visible light, it results in the excitation of fluorescent biological molecules known as fluorophores. They absorb the energy and emit it in the form of fluorescent light of longer wavelengths. This property can be effectively employed in the diagnosis of tissues under various conditions. FTIR spectroscopy offers an elegant and easy approach to clinical analysis. The use of FTIR spectroscopy for biomedical applications has increased tremendously in recent years. FTIR spectrum exhibits characteristic absorption frequencies depending on the difference in their functional groups present in the sample. These techniques can be employed to identify the analytesÂ Â present in the sample. FTIR spectroscopy can be effectively employed in the tissue analysis. The FTIR spectrum of the tissue is used as a fingerprint in the identification of normal tissue and that affected with the diseased sample. In the present work, both infrared and fluorescence spectroscopy have been employed in the analysis of tissue of different organs of rat. The experimental studies have been carried out on different types of tissue samples such normal, tumor induced and tumor treated cases. The study shows that the spectral profiles are different when the tissue of a particular organ is affected with tumor. But on treatment, the approach of the spectra to the normal condition clearly establishes the effectiveness of the treatment.